2022
DOI: 10.3390/agronomy12081844
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Composition and Biosynthesis of Alkaloids and on the Taxonomy, Domestication, and Cultivation of Medicinal Fritillaria Species

Abstract: Fritillaria is a perennial herb with medicinal properties. There are 158 Fritillaria species worldwide, 33 of which have reported therapeutic efficacy. Alkaloids are the principal constituents in Fritillaria. Fritillaria species growing at 2700–4000 m are the sources of extract namely Chuan Beimu (the Pharmacopoeia of the People’s Republic of China, 2020 Edition), with low biomass, mainly containing more 5α-cevanine isosteroidal alkaloids with cis-configuration. In contrast, species growing below 1500 m are us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…The Fritillaria genus, membership of the Liliaceae family, is broadly spread in Asia, North America, and Europe, encompassing a total of 158 species. [6] Past chemical investigations to Fritillaria plants have unveiled lots of compounds, including isosteroidal, steroidal, and amide alkaloids, lignans, triterpenoids as well as diterpenoids. [7][8][9][10][11][12] Alkaloids are the principal constituents in Fritillaria.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Fritillaria genus, membership of the Liliaceae family, is broadly spread in Asia, North America, and Europe, encompassing a total of 158 species. [6] Past chemical investigations to Fritillaria plants have unveiled lots of compounds, including isosteroidal, steroidal, and amide alkaloids, lignans, triterpenoids as well as diterpenoids. [7][8][9][10][11][12] Alkaloids are the principal constituents in Fritillaria.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Alkaloids are the principal constituents in Fritillaria. [6] Fritillaria przewalskii Maxim. ex Batal., known colloquially as MinBei, widely growing in the provinces of Gansu, Sichuan, and Qinghai in China, and is one of the main sources of the medicinal herb "Chuan Beimu", included in the 2020 Edition of Pharmacopoeia of the People's Republic of China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more promising approach for obtaining structurally complex natural products is the combination of genetic and metabolic engineering [11][12][13][14]. Because of the impact of the environment, Fritillaria is represented in China by various cultivars and variations, each of which has distinct qualities [15]. A multi-species metabolomics investigation revealed that F. cirrhosa contains abundant steroidal alkaloids, such as imperialine, suggesting that F. cirrhosa D. Don might be considered a suitable plant material for research on FISA biosynthesis [14].…”
Section: Introductionmentioning
confidence: 99%
“…ISA is then produced via initial cyclization of the central intermediate cycloartenol to cholesterol, followed by hydroxylation, oxidation, and transamination [14]. The majority of the research has been devoted to the cloning and control of functional genes upstream of the terpenoid biosynthesis pathway, including the 3-hydroxy-3-methylglutaryl coenzyme A reductase gene (HMGR), farnesyl diphosphate synthase (FPS), squalene synthase (SS), and cycloartenol synthase (CAS) [15]. Secondary metabolic pathways following cycloartenol generation are rarely studied, particularly the downstream CYP450 genes responsible for C-22, C-23, and C-26 hydroxylation in the steroidal alkaloid biosynthesis pathway.…”
Section: Introductionmentioning
confidence: 99%